Pengaruh Debt To Equity Ratio Dan Return On Equity Terhadap Kebijakan Dividen Pada Pt. United Tractors Tbk Periode 2010-2024 - Reza Al-Afgani, Muhammad; Irnawati, Jeni (Jurnal SEKURITAS (Saham, Ekonomi, Keuangan dan Investasi), 2025)
This study aims to examine the Effect of Debt to Equity Ratio and Return on Equity on Dividend Policy at PT. United Tractors Tbk for the 2010-2024 Period. The data used are secondary data obtained from the site https://www.unitedtractors.com. The sampling method is purposive sampling. The data analysis method used is multiple linear regression. This study uses a times series data regression method assisted by the SPSS 23 program. Based on the results of the study, it shows that: 1) Debt to Equity Ratio has a negative and significant effect on the dividend policy of PT. United Tractors Tbk for the 2010–2024 period, with t count -2.636> t table 2.719 and a significance of 0.022 <0.05; 2) Return on Equity has a positive and significant effect on dividend policy, with t count 2.555> t table 2.719 and a significance of 0.025 <0.05; 3) Debt to Equity Ratio and Return on Equity simultaneously have a positive and significant effect on dividend policy, as indicated by the calculated F of 4.145 > F table 3.88 and a significance level of 0.043 < 0.05. The Adjusted R Square value of 0.310 indicates that DER and ROE explain 31% of the variation in dividend policy, while other factors outside the model influence the remaining 69%.